The Effect of Transfers and Workload on the Performance of Cooperative Office Employees - Ahasyweros, Limkon; Pagiu, Chrismesi; Pundissing, Rati (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The purpose of this study was to determine whether there was an influence of mutation and workload on employee performance at the Balo' Ta Savings and Loans Cooperative Head Office. Data collection procedures in this study included observation, questionnaires, and documentation. The method used was a quantitative method with multiple linear regression analysis processed using SPSS 25. This study was conducted at the Balo' Ta Savings and Loans Cooperative Head Office, Tana Toraja Regency with a sample of 32 respondents. The sampling technique used was purposive sampling. The results of the calculation with the t test showed that for the mutation variable, the t count value (0.892) < t table (1.699), while for the workload variable, the t count value (6.541) > t table (1.699). The conclusion of this study is that mutation does not affect employee performance, while workload affects employee performance. Simultaneously, mutation and workload affect employee performance at the Balo' Ta Savings and Loans Cooperative Head Office, Tana Toraja Regency.